Ambrosiella roeperi: An Unreported Fungus Isolated from Ambrosia Beetles - Ju-Heon Lee; YoungSoo Kim; Leonid N. Ten; Jong-Taek Park; Dong-Hyuk Le; Hee-Young Jung (한국균학회지)
In this study, ambrosia beetles were collected using insect traps in Gunwi-gun, Daegu-si, South Korea, to investigate symbiotic fungi associated with beetles. Fungi were isolated from the collected beetles. Among the isolates, a strain obtained from Ambrosiodmus rubricollis was designated as ARI-24-A4. Cultural and molecular biological analyses confirmed that ARI24-A4 belongs to Ambrosiella. Key morphological characteristics, including the structure of the conidiophores and the size of aleurioconidia (av. 12.9 μm × 12.5 μm), were examined to accurately identify the Ambrosiella species. A phylogenetic tree was constructed by combining the internal transcribed spacer (ITS) region, translation elongation factor 1-alpha (TEF1-α), and small subunit of nuclear ribosomal RNA (SSU) gene sequences to confirm the phylogenetic position. The strain was verified to share the same phylogenetic position as Ambrosiella roeperi. Therefore, ARI-24-A4 was confirmed to be A. roeperi, a species previously unreported in Korea. It has been recorded as a newly identified species in the country.